2010
DOI: 10.2202/1553-3840.1444
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Evaluation of Two Red Seaweeds for Their Cytotoxic and Antioxidant Activities In Vitro

Abstract: This article evaluates the cytotoxic and antioxidant activities of the seaweeds Amphiroa fragilissima and Asparigopsis taxiformis methanolic extracts in-vitro. The aim of this study was to test the selected red seaweed extracts for their cytotoxic activity by Brine shrimp lethality assay and antioxidant properties by in-vitro free radical scavenging assays such as, 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, reducing power assay, and metal ion chelating assay. Also, the total phenolic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In some cases the antiproliferative activity of alga extracts has been positively correlated with total polyphenol content, suggesting a causal link between extract content of polyphenols and phenolic acids [14]. This causal link has also been found with the cytotoxicity in vitro of some red and brown algae extracts [23, 24]. Moreover, phenolic compounds including phlorotannins can induce oxidative stress in cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the antiproliferative activity of alga extracts has been positively correlated with total polyphenol content, suggesting a causal link between extract content of polyphenols and phenolic acids [14]. This causal link has also been found with the cytotoxicity in vitro of some red and brown algae extracts [23, 24]. Moreover, phenolic compounds including phlorotannins can induce oxidative stress in cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, seaweeds rich in carotenoids, polyphenols, polysaccharides, triterpenes are more inclined to possess angiosuppressive activity. A number of studies have indicated that marine seaweeds from India exhibit potent antioxidant properties [ 12 , 13 , 14 , 15 , 23 , 24 , 25 ]; however, they have not been systematically explored for their angiosuppressive potential. To the best of our knowledge, this is the first report on the angiosuppressive properties of marine Indian seaweed extracts.…”
Section: Introductionmentioning
confidence: 99%